2022
DOI: 10.1038/s41467-021-27132-8
|View full text |Cite
|
Sign up to set email alerts
|

A de novo paradigm for male infertility

Abstract: De novo mutations are known to play a prominent role in sporadic disorders with reduced fitness. We hypothesize that de novo mutations play an important role in severe male infertility and explain a portion of the genetic causes of this understudied disorder. To test this hypothesis, we utilize trio-based exome sequencing in a cohort of 185 infertile males and their unaffected parents. Following a systematic analysis, 29 of 145 rare (MAF < 0.1%) protein-altering de novo mutations are classified as possibly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
42
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 66 publications
(95 reference statements)
0
42
0
3
Order By: Relevance
“…In our cohort of 77 patients, 51 patients were confirmed to suffer from nonobstructive severe oligospermic or azoospermic phenotypes. In the original publication related to this study (Oud et al, 2022), we showed that six out of the eight likely causative DNMs identified in these patients were of paternal origin (Supporting Information: Tables S9 and S14, Figure S7). As DNMs predominantly cause a dominant effect, it suggests that DNMs with a deleterious effect on the health of an individual can escape negative selection in spermatids from the paternal germline.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In our cohort of 77 patients, 51 patients were confirmed to suffer from nonobstructive severe oligospermic or azoospermic phenotypes. In the original publication related to this study (Oud et al, 2022), we showed that six out of the eight likely causative DNMs identified in these patients were of paternal origin (Supporting Information: Tables S9 and S14, Figure S7). As DNMs predominantly cause a dominant effect, it suggests that DNMs with a deleterious effect on the health of an individual can escape negative selection in spermatids from the paternal germline.…”
Section: Discussionmentioning
confidence: 85%
“…). It has been shown that approximately 80% of DNMs are of paternal origin (Goldmann et al, 2016;Kong et al, 2012;Oud et al, 2022;Yuen et al, 2016). A major factor known to contribute to an increase in DMNs in individuals is advanced parental age at the time of conception, particularly paternal age (Goldmann et al, 2016;Kong et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we provide a higher confidence list of 21 genes which have all been observed in multiple NOA cases and have nominally significant association with NOA in a comparison with 11,587 fertile controls (Supplementary Table 4 ). The observed detection rate of possible causes of NOA in GEMINI (20%) remains a conservative estimate, as our approach did not consider genes exclusively involved in fetal gonad development, excluded genes with broad expression across the body, and did not address dominant or additive defects likely to contribute to the manifestation of NOA as well 47 , 48 . A more detailed analysis of X-linked genes is reported in a companion paper focusing exclusively on the X chromosome, using a different method of prioritization than described here 49 .…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that in our study, the segregation of the identified variants could only be achieved in 40% of cases because the parents were not available for the other patients. The absence of available trios has hampered the assessment of de novo mutations that might explain a subset of POI as has been observed in infertile men 66 or other conditions 67 and may improve the diagnostic performance of NGS studies in POI.…”
Section: Discussionmentioning
confidence: 99%